2018
DOI: 10.1111/jce.13476
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation use and clinical outcomes after catheter ablation in patients with persistent and longstanding persistent atrial fibrillation

Abstract: Anticoagulation discontinuation in well selected, closely monitored patients following successful ablation of nonparoxysmal AF was associated with a low rate of clinical embolic CVEs. Prospective studies are required to confirm safety of OAT discontinuation after successful AF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 45 publications
1
31
1
Order By: Relevance
“…In the study by Liang et al., it was reported that 7 patients experienced thromboembolic stroke, 4 in patients who were on therapeutic anticoagulation. It is not clear to the reader why these patients had stroke during therapeutic AC.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…In the study by Liang et al., it was reported that 7 patients experienced thromboembolic stroke, 4 in patients who were on therapeutic anticoagulation. It is not clear to the reader why these patients had stroke during therapeutic AC.…”
supporting
confidence: 82%
“…Liang et al . in this issue of Journal of Cardiovascular Electrophysiology , evaluated whether OAC therapy can be safely discontinued in patients rendered free of AF recurrences and examined long‐term rates of stroke and major bleeding episodes in patients with nonparoxysmal AF treated with catheter ablation.…”
mentioning
confidence: 99%
“…Some studies in our analysis included several patients with mechanical heart valves, which precluded the discontinuation of OAC, a fact that was confirmed by contacting the corresponding authors. The paper by Gallo et al was the only that excluded patients with mechanical heart valves from its analysis.…”
Section: Limitationsmentioning
confidence: 85%
“…Hunter et al used a multicenter registry in the UK and Australia. Liang et al used data collected in the University of Pennsylvania. Gallo et al retrospectively analyzed data from three Italian registries: Cardinal Massaia Hospital of Asti, Mauriziano Hospital of Turin and Città della Salute e della Scienza Hospital of Turin.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Liang et al, 5 it was reported that 7 patients experienced thromboembolic stroke, 4 in patients who were on therapeutic anticoagulation. It is not clear to the reader why these patients had stroke during therapeutic AC.…”
mentioning
confidence: 99%